Reactive polymer enhanced miscible displacement in porous media - De, Debnath (My University, 1996)
The displacement of aqueous Kraft model black liquor (MBL) from a porous bed with cationic polymer solution (polyDADMAC) was investigated to determine the mechanisms by which polyDADMAC influenced the miscible displacement. The porous bed consisted of a 1.7 cm diameter central channel of 638 μm glass beads surrounded by an annulus of 121 μm glass beads contained in a 5.2 cm internal diameter cylindrical glass column. Flow visualization experiments and displacement washing experiments were performed. Conductivity probes were installed at twelve locations inside the beds to monitor the velocity and locations of displacement fronts. Flow visualization experiments in a transparent cell gave direct evidence of the presence of cross flow of fluid elements from annulus to the channel in a model channel bed during water displacement. After selective plugging of the channel with precipitate formed from reaction of lignin and polyDADMAC, fluid elements in annulus were observed to move straight down the model channel bed. Results of the displacement experiments in the model beds confirmed that washing efficiency, a measure of the miscible displacement performance, increased by 1.7 to 2 times and permeability of channel decreased by 34% to 18% when the bed was displaced with polymer solution instead of water. The improvement in the displacement performance with polymer solution resulted due to the reduction in channeling of polymer solution in the model channel bed. Results of data obtained by the probes gave direct evidence of the reduction in velocity and mixing length of front in the channel confirming reduction in the channeling in a model channel bed during displacement with polymer solution. Increased velocity of front in the annulus during displacement with polymer solution confirmed better miscible displacement in a channel bed with polymer solution than that with water. A communicating channel bed model was developed based on a technique called network of zones. The model predicts the breakthrough curves and the profiles of interstitial velocities inside the model beds during different displacement washing conditions. The model successfully predicts pressure drop profiles across homogeneous beds during displacement with either water or polymer solution and channel bed during washing with water. However, the pressure drop predicted by the model was higher than that obtained experimentally during washing with polymer solution in a model channel bed.
Keywords: Chemical Engineering; Chemical Engineering